The Effect of Job Satisfaction in Mediating the Relationship Between Leadership, Organizational Support and Work Motivation - Ernest Grace; Nelly Ervina; Markus Doddy Simanjuntak; Julyanthry Julyanthry; Injen Pardamean Butarbutar (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Job satisfaction is a critical factor influencing employee motivation and organizational outcomes, yet its role as a mediator between leadership, organizational support, and work motivation remains underexplored, particularly in developing economies. This study aims to examine how job satisfaction mediates the relationship between leadership styles, organizational support, and work motivation through a systematic literature review of empirical studies published between 2015 and 2024. The review analyzed 17 peer-reviewed articles selected from academic databases using predefined inclusion criteria, focusing on empirical studies involving job satisfaction as a mediator. Findings reveal that job satisfaction consistently serves as a psychological bridge, linking leadership styles, such as transformational and transactional, and organizational support to enhanced employee motivation, commitment, and performance, particularly in Southeast Asian contexts like Indonesia and Malaysia. The review highlights diverse industry settings, including hospitality and public services, emphasizing the broad applicability of the mediation model. This study concludes that job satisfaction is a pivotal mechanism for translating organizational strategies into positive employee outcomes, offering a framework for future research to explore causal pathways and cross-cultural variations in organizational behavior.